Peran Mediasi Hubungan Interpersonal Dalam Hubungan Antara Keselamatan Kerja Dan Kepuasan Kerja Karyawan - Abdul Halik; Suprianto; Eka Hadiwijaya; Taufik Andriadi (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the effect of Occupational safety on employee job satisfaction by considering the mediating role of interpersonal relationships. This study uses an explanatory quantitative approach with data collected through a survey of 92 employees at PT PLN (Persero) UP3 Sumbawa. The results of the analysis using Partial Least Squares (PLS) show that there is a positive and significant direct effect of Occupational Safety variables on Interpersonal Relationships with Colleagues, Occupational Safety on Interpersonal Relationships with Supervisors, Interpersonal Relationships with Colleagues on Job Satisfaction, and Interpersonal Relationships with Supervisors on Job Satisfaction. Meanwhile, the direct effect of Occupational Safety variables on Job Satisfaction is positive but not significant. Furthermore, in the analysis of the role of mediating variables, it is found that interpersonal relationships with colleagues do not mediate the (indirect) relationship of Occupational safety to job satisfaction. While interpersonal relationships with superiors fully or perfectly mediate (complete mediation) the (indirect) relationship of Occupational safety to job satisfaction. This finding highlights the importance of social aspects in the organization as a supporting factor for Occupational safety in increasing employee job satisfaction.